MODELLING OF TOURISM REGION: CASE OF NOVI SAD GRAVITATIONAL ZONE - Garača, Vuk; Vukosav, Svetlana; Stamenkovic, Igor Ljubomir; Bradić, Milan (Turizam, 2019)
Significant tourist centers are inseparably linked with their gravitational zone, which together make up a tourist destination, or tourist region. The tourist region is a complex spatial unit, composed of a number of elements, such as primary, secondary and tertiary tourist centers, then gateways of tourist flows, intraregional network of roads, as well as directions that make tourist flows to the region of the tourist region. Therefore, the formation of a tourist region model on previous element and ideas must be the basis for the development of tourism in each tourist center, which has predispositions to be primary. The subject of this work is the modeling of the tourist region of Novi Sad, where the spatial coverage of work is limited to the gravitational zone of this city. The task of the paper is to determine the level of the centrality of tourist sites within the Novi Sad tourist region. Keywords: tourist region, modeling, level of centrality, gravitational zone, Novi Sad.